Rozwiaz równania:
a) 4x+3=11
b) 2x-9=12
c) 6x+4=2x-3
d) 5x+5x+3x=4x+18
e) 10x-3=2
f) 11+6y=y+15+7y+26
g) 30-5z=2-3z
h) 1-x+5+2x=-7-2x
i) 9-2m=5-m
j) 3x-9+7x=2+4x+3
k) x-4+9-6x=6x-6
l) 10n-3-2n=3n-13+2n
m) 6r-4-3r=3r+12+4r
n)3-5y-8y+4+4y=25
o)-16+15x+4x+22=8x-27
p)7p-18+3p-28-5p-8p=2p
r)5r-3+2r=4r+9-r
s)3x-2+5x=4x+8-x
t)4t-18+7t=3+9t-15
u)8z-12+7=15z+9
w)-6w+13-2w=13-5w+15
z)7z+6+4z=9-2z+10
Zadanko na jutro prosze o szybkie rozwiazanie

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-26T19:34:55+01:00
A) 4x+3=11
11-3=4x
8=4x /:4
x=2
b) 2x-9=12
2x=12+9
2x=21 /:2
x=10,5
c) 6x+4=2x-3
4x=1 /:4
x=1/4
d) 5x+5x+3x=4x+18
9x=18 /:9
x=2
e) 10x-3=2
10x=5 /:10
x=0,5
f) 11+6y=y+15+7y+26
-2y=30 /:-2
y=15
g) 30-5z=2-3z
-2z=-28 /:-2
z=14
h) 1-x+5+2x=-7-2x
-x=-13 /*-1
x=13
i) 9-2m=5-m
m=-4
j) 3x-9+7x=2+4x+3
6x=14 / :6
x=14/6
k) x-4+9-6x=6x-6
-11x=-11 /:-11
x=1
l) 10n-3-2n=3n-13+2n
3n=-10 /:3
n=-10/3
m) 6r-4-3r=3r+12+4r
-4r=16 /:-4
r=-4
n)3-5y-8y+4+4y=25
-9y=18 /:-9
y= -2
o)-16+15x+4x+22=8x-27
11x=-21 /:11
x=-21/11
p)7p-18+3p-28-5p-8p=2p
-3p=48 /:3
p=16
r)5r-3+2r=4r+9-r
4r=12 /:4
r=3
s)3x-2+5x=4x+8-x
5x=10 /:5
x=2
t)4t-18+7t=3+9t-15
2t=6 /:2
t=3
u)8z-12+7=15z+9
-7z=14 /:-7
z=-2
w)-6w+13-2w=13-5w+15
3w=15 /:3
w=5
z)7z+6+4z=9-2z+10
2010-01-26T20:00:29+01:00
A) 4x= -3+11
4x= 8/:4
x=2
b) 2x=9+12
2x= 21/:2
x=10,5
c)6x-2x=-4-3
4x=-7/:4
x=-1,75
d)5x+5x+3x-4x=18
9x=18/:9
x=2
e) 10x=3+2
10x=5/:10
x=0,5
f)6y+y-7y=-11+15+26
0=30 rozwiazanie sprzeczne
g)-5z+3z=-30+2
-2z=-28/:-2
z=14
h) -x+2x-2x=-1-5-7
-x=-13

i) -2m+m=-9+5
-m=-4
j) 3x=7x-4x=9+2+3
6x= 14/:6
x=2.(3)
k) x-6x-6x=4-9-6
11x=11/:11
x=1
l)10n-2n-3n-2n=3-13
2n=10/:2
n=5
m) 6r-3r-3r-4r=4+12
-4r=16/: -4
r=-4
n) 5y-8y+4y=-3-4+25
y=18
o) 15x+4x-8x=16-22-27
11x=33/11
x=3
p) 7p+3p-5p-8p-2p=18+28
-5p=46/:5
p=9,2
r) 5r+2r-4r=3+9-6
3r=6/:3
r=2
s)3x+5x-4x+x=2+8
5x=10/:5
x=2
t) 4t+7t-9t=18+3-15
2t=6/:2
t=3
u) 8z-15z=12-7+9
-7z=14/:-7
z=-2
w)-6w-2w+5w=-13+15+13
-3w=15/:-3
w=-5
z)7z+4z+2z=-6+9+10
13z=13/:-13
z=1
2010-01-26T20:50:53+01:00
A) 4x+3=11
11-3=4x
8=4x /:4
x=2
b) 2x-9=12
2x=12+9
2x=21 /:2
x=10,5
c) 6x+4=2x-3
4x=1 /:4
x=1/4
d) 5x+5x+3x=4x+18
9x=18 /:9
x=2
e) 10x-3=2
10x=5 /:10
x=0,5
f) 11+6y=y+15+7y+26
-2y=30 /:-2
y=15
g) 30-5z=2-3z
-2z=-28 /:-2
z=14
h) 1-x+5+2x=-7-2x
-x=-13 /*-1
x=13
i) 9-2m=5-m
m=-4
j) 3x-9+7x=2+4x+3
6x=14 / :6
x=14/6
k) x-4+9-6x=6x-6
-11x=-11 /:-11
x=1
l) 10n-3-2n=3n-13+2n
3n=-10 /:3
n=-10/3
m) 6r-4-3r=3r+12+4r
-4r=16 /:-4
r=-4
n)3-5y-8y+4+4y=25
-9y=18 /:-9
y= -2
o)-16+15x+4x+22=8x-27
11x=-21 /:11
x=-21/11
p)7p-18+3p-28-5p-8p=2p
-3p=48 /:3
p=16
r)5r-3+2r=4r+9-r
4r=12 /:4
r=3
s)3x-2+5x=4x+8-x
5x=10 /:5
x=2
t)4t-18+7t=3+9t-15
2t=6 /:2
t=3
u)8z-12+7=15z+9
-7z=14 /:-7
z=-2
w)-6w+13-2w=13-5w+15
3w=15 /:3
w=5
z)7z+6+4z=9-2z+10